bT- compactness and bT - connectedness in Supra Topological Spaces (European Journal of Pure and Applied Mathematics, 2017)
In this paper we newly originate the notion of bT - compact space and in-spected its several eects and characterizations. Also we newly originate andstudy the concept of bT - Lindelof spaces and Connected spaces.
Keywords: bT -open sets; bT -compact spaces; bT - Lindelof spaces and bT - connected spaces.